2013
DOI: 10.1586/1744666x.2014.857602
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of B cells in atherosclerosis: potential clinical implications

Abstract: Atherosclerosis is a progressive inflammatory disease of the medium to large arteries that is the largest contributor to cardiovascular disease (CVD). B cell subsets have been shown in animal models of atherosclerosis to have both atherogenic and atheroprotective properties. In this review we highlight the research that developed our understanding of the role of B cells in atherosclerosis both in humans and mice. From this we discuss the potential clinical impact B cells could have both as diagnostic biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 117 publications
0
12
0
Order By: Relevance
“…B-1a cells produce IgM NAbs in an antigen-independent manner, whereas B-1b cells respond to T cell-independent antigens providing them the capacity to form memory 12, 38 . The work of Haas et al 33 and Alugupalli et al 39 established B-1b cells as the source of T cell-independent memory and support B-1b cells as targets of T cell-independent antigen directed vaccination, which has been discussed as a novel therapeutic against atherosclerosis 18, 19, 30, 40 . As such, understanding the impact of B-1b cells on atherosclerosis and elucidating factors that regulate their activity is of clear importance.…”
Section: Discussionmentioning
confidence: 99%
“…B-1a cells produce IgM NAbs in an antigen-independent manner, whereas B-1b cells respond to T cell-independent antigens providing them the capacity to form memory 12, 38 . The work of Haas et al 33 and Alugupalli et al 39 established B-1b cells as the source of T cell-independent memory and support B-1b cells as targets of T cell-independent antigen directed vaccination, which has been discussed as a novel therapeutic against atherosclerosis 18, 19, 30, 40 . As such, understanding the impact of B-1b cells on atherosclerosis and elucidating factors that regulate their activity is of clear importance.…”
Section: Discussionmentioning
confidence: 99%
“…Natural antibodies directed against antigens associated with these three classes of disease appear to be functional. (1) In mice, a number of adoptive transfer experiments with Apoe −/− recipients have led to the generally accepted paradigm that B-1 cells and the IgM antibodies they produce are atheroprotective, whereas B-2 cells and the IgG antibodies they produce are atherogenic ( 50 , 51 ). Less invasive studies have been carried out with people, and it has been shown that human IgM anti-oxLDL is inversely correlated with cardiovascular and carotid disease ( 12 , 38 , 39 , 52 54 ), whereas IgG has been found to be positively correlated with atherosclerosis ( 12 , 52 , 55 60 ) or not correlated at all with vessel pathology ( 40 , 61 64 ).…”
Section: Disease-associated Natural Antibodies Are Functionalmentioning
confidence: 99%
“…Lymphocytes comprise a range of different cell types with different roles in the immune system 14. Low total lymphocyte count is associated with malnutrition and immune suppression,15 and observational studies have shown that it is associated with poor prognosis in patients with ST elevation MI 16.…”
Section: Introductionmentioning
confidence: 99%